CORAL REEFS DIVERSITY IN GILI GENTING ISLAND SUMENEP MADURA - Fathorrohman Fathorrohman; Romaidi Romaidi; Bayyinatul Muchtaromah (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2013)
Coral reef ecosystem is the most threatened ecosystem among marine ecosystem in the world due to the combination of anthropogenic and natural disturbances. More research is needed to be monitor ed and assess coral reef ecosystems, which will be used to fin d understanding of the ecological integrity and further improvement of the protection strategy in the future. This re search was aimed to know the diversity of coral reef diversity at Gili Genting Island Sumenep Madura and evaluate the condition of coral reef ecosystem based on cover the percentage. Line intercept method was used to understand coral reef diversity and its condition in the desired observation station. The result revealed that 9 families, 22 genera and 4 5 species of coral have been successfully found, in which Acropora is the most common genus found in in Gili Genting Island . The cover percentage analysis also indicated that the condition of coral reef ecosystem in Gili Genting Island could be classified to very bad category where th e total average of cover percentage is 12.55%. These findings provide the prelim inary information about the condition of coral reef ecosystem in small i sland that might be useful for the future integrated management based on ecological perspective.